Automated calibration of baseline model for energy conservation using multi-objective Evolutionary Programming (EP) / Ahmad Amiruddin Mohammad Aris - Mohammad Aris, Ahmad Amiruddin (2019)
This thesis presents multi-objective optimization approach in developing baseline energy using multi-objective Evolutionary Programming (EP). The co-simulation approach is proposed to obtain optimal solution of the thermal comfort-baseline energy configuration due to complexity in finding the trade-off between variables in reducing discrepancies between simulated energy consumption and measured data, furthermore leveraging automated computational calibration process. The proposed co-simulation process is developed by coupling building energy simulation (BES) software, Energy Plus with multi-objective evolutionary programming (MOEP) algorithm which is implemented in Matlab using coupling software, BCVTB. The proposed optimization approach is applied to a single storey Green Energy Research Centre (GERC) office building located in UiTM Shah Alam with multiple characteristics of fully conditioned and partially conditioned buildings. The office consists of five different size rooms with different purposes. In this regard, three building parameters are taken as decision variables including occupancies, lightings and electrical equipment. Meanwhile, output from Energy Plus i.e. hourly energy consumption and Predicted Percentage of Dissatisfied (PPD) are investigated as single and multi-objective optimization. The MOEP objective function is set to minimize the difference between simulated and measured energy consumption considering human thermal comfort in the building by using sum-weighted decision technique. To evaluate the accuracy of building energy model, hourly criteria for Normalized Mean Biased Error (NMBE) and Coefficient of Variance Root Mean Squared Error (CV(RMSE)) as proposed by the IPMVP are used. In the single objective approach, automated calibration method considering minimum baseline energy triumph over all other methods with NMBE and CV(RMSE) at 4.52 % and 10.8% respectively, hence meeting the acceptable range set by the IPMVP. The baseline energy is said calibrated and can be used for retrofit analysis. In multi objectives approach, MOEP with fixed weight SWA technique is the best alternative to solve multi-objectives problem for baseline calibration with NMBE and CV(RMSE) of 3.02% and 4.64% respectively. This study is also extended to investigate potential saving from two ECMs, 20w LED lighting and 5kW PV panel using the best variables configuration obtain from previous stage.